PERAN AKREDITASI DAN BUDAYA MUTU DALAM MENINGKATKAN KINERJA PERGURUAN TINGGI - Farwitawati, Reni; Arini, Arini; Masirun, Masirun; Fithrie, Souvya (Universitas Lancang Kuning, 2024)
This study aims to examine the effect of accreditation on university performance directly and indirectly through quality culture as a mediator. This research is a quantitative study that uses sampling techniques referring to the advice of (Hair, 2010) which states that in survey research, the ideal sample size is between 5 to 20 times the number of items of all research variables used. The population of this study were all private universities in Pekanbaru. Determination of sample size. This study determines the option of 10 x 12 items from the 3 research variables used, so that the minimum sample size targeted is 120 respondents. The data were analyzed using a structural equation model with a test tool using partial least square (PLS). The conclusion of this study supports all hypothesized relationships, such as the effect of accreditation on college performance and quality culture, the effect of quality culture on college performance, and the indirect effect of accreditation on college performance through quality culture. Although several studies have highlighted the important role of accreditation in the literature, accreditation alone cannot improve college performance in Indonesia, and Pekanbaru is no exception